A wear-resistant braided ceramic material and preparation method thereof
By using immersion and orthogonal braiding technology of carbon fiber and basalt fibers in braided ceramic materials, combined with specific ceramic body formulas and sintering treatments, the problem of difficult to balance the wear resistance, toughness and soil resistance of existing ceramic materials is solved. It significantly improves the stability and efficiency of the product.
Patent Information
- Application Number
- CN202411689557.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The wear resistance, toughness and soil resistance of existing braided ceramic materials are difficult to balance, and the stability of ultraviolet resistance and cold and heat cycle resistance is poor, which limits the efficiency of the product.
Carbon fiber and basalt fiber are used to immerse it in the ceramic body respectively, and then sintered and improved treatment is carried out to prepare wear-resistant braided ceramic materials. The ceramic body consists of boron nitride, alumina, tungsten carbide, zirconia and doped modified nanotitanium dioxide additives. The performance of the ceramic body is optimized through the coordination of specific ball milling and liquid regulation and modification regulators.
The balance between wear resistance, toughness and soil resistance of wear-resistant braided ceramic materials has been improved, and the UV resistance and cold and heat cycle stability of the product has been significantly improved, and the product's use efficiency has been improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a wear-resistant braided ceramic material and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain, and is also a kind of arts and crafts in my country. As early as the Neolithic Age, my country already had rough and simple painted pottery and black pottery. Pottery and porcelain have different textures and properties. Pottery is made of clay with high viscosity and strong plasticity as the main raw material. It is opaque, has fine pores and weak water absorption, and has a turbid sound when struck. Porcelain is made of clay, feldspar and quartz, and woven ceramic materials are a type of ceramics. The clay is made into thin strips and then woven into various shapes. The existing woven ceramic materials have poor wear resistance. At the same time, it is difficult to balance and improve the wear resistance, toughness and anti-fouling performance of the product. The product has poor UV resistance and cold and hot cycle stability, which limits the use efficiency of the product. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide a wear-resistant braided ceramic material and a preparation method to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a method for preparing a wear-resistant braided ceramic material, comprising the following steps:
[0006] Step 1: Preparation of ceramic body:
[0007] (1) Weigh the raw materials according to weight:
[0008] 15-20 parts of boron nitride, 5-8 parts of aluminum oxide, 4-7 parts of additives for doping and modifying nano titanium dioxide, 2-5 parts of tungsten carbide, 2-4 parts of zirconium oxide and 8-12 parts of ball milling leveling liquid;
[0009] (2) The above raw materials are mixed and ball-milled at a speed of 1500 r / min for 1 h to obtain a ceramic body;
[0010] Step 2: Immersing the carbon fiber and the basalt fiber into the ceramic body for immersion treatment, and after the immersion is completed, an immersed carbon fiber body and an immersed basalt fiber are obtained respectively;
[0011] Step three: three-dimensionally orthogonally weave the immersed carbon fiber body and the immersed basalt fiber, and after weaving, sinter and improve the process to obtain a wear-resistant braided ceramic material.
[0012] Preferably, the specific steps of the sintering improvement treatment are:
[0013] First, sinter at 350℃ for 20-30min, then heat to 550-570℃ at a rate of 2-5℃ / min and keep at this temperature for 35min;
[0014] Then, heat up to 1200-1250℃ at a rate of 1-3℃ / min, keep warm for 1h, and finally air cool to room temperature.
[0015] The immersion ultrasonic power of the immersion treatment in step 2 is 450-500W, and the immersion time is 30-50min.
[0016] Preferably, the preparation method of the synergist of the doped modified nano titanium dioxide is:
[0017] S01: Add 2-4 parts of nano-silica sol and 1-3 parts of chitosan solution with a mass fraction of 2-5% to 5-8 parts of sodium alginate solution with a mass fraction of 6% by weight and stir well to obtain modified nano-silica sol;
[0018] S02: preheating nano titanium dioxide at 60-65°C for 10-15 minutes, and heat-insulating to obtain preheated nano titanium dioxide; adding 3-5 parts of preheated nano titanium dioxide and 1-3 parts of citric acid to 4-7 parts of modified nano silica sol by weight, and mixing well to obtain nano titanium dioxide modified liquid;
[0019] S03: Preparation of additives:
[0020] S031: fully stirring the nano-sericite in a sufficient amount of a 5% by mass hydrogen peroxide solution, then washing, filtering, and drying to obtain dried nano-sericite; irradiating the dried nano-sericite in a proton irradiation box at an irradiation power of 350-400 W and an irradiation time of 10-15 min to obtain pretreated nano-sericite;
[0021] S032: adding 4 to 7 parts of pretreated nano-sericite, 2 to 4 parts of lanthanum chloride solution and 2 to 3 parts of silicon powder to 5 to 8 parts of dopamine hydrochloride solution by weight, stirring and modifying, after stirring, filtering and drying to obtain an additive;
[0022] S04: Mix the additive and the nano-titanium dioxide modified liquid in a weight ratio of 5:(2-4) and perform ball milling. After the ball milling is completed, wash with water, filter and dry to obtain the additive of doped modified nano-titanium dioxide.
[0023] Preferably, the ball milling speed of the mixing ball milling treatment in S04 is 550-650 r / min, and the ball milling is 1-2 h.
[0024] Preferably, the mass fraction of the lanthanum chloride solution is 2-4%; the mass fraction of the dopamine hydrochloride solution is 4-6%; the stirring speed of the stirring modification treatment is 450-500 r / min, and the stirring time is 35-40 min.
[0025] Preferably, the preparation method of the ball milling leveling solution is:
[0026] S11: prepare 3-5% by mass sodium dodecylbenzene sulfonate solution and 6% by mass sodium citrate solution;
[0027] S12: 2 to 5 parts of sodium carboxymethyl cellulose, 3 to 5 parts of sodium dodecylbenzene sulfonate solution, 1 to 2 parts of silane coupling agent KH550 and 2 to 4 parts of sodium citrate solution are uniformly stirred by weight to obtain a ball milling medium;
[0028] S13: The modified regulator and the ball milling medium are stirred and mixed thoroughly in a weight ratio of 2:5 to obtain a ball milling leveling solution.
[0029] Preferably, the preparation method of the modified regulator is:
[0030] The graphene is first stirred in a sufficient amount of acid solution, then washed with water, filtered and dried to obtain dry graphene; 3-5 parts of dried graphene, 1-2 parts of nano whiskers and 5-8 parts of yttrium nitrate solution are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours, and after the ball-milling is completed, washed with water, filtered and dried to obtain a modified regulator;
[0031] The preparation method of the nano whisker body is as follows: nano silicon carbide whiskers and sodium silicate solution are mixed thoroughly in a weight ratio of 2:5 to obtain the nano whisker body.
[0032] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium silicate solution is 3-4%.
[0033] Preferably, the acid solution is a 5% by mass sulphuric acid solution.
[0034] The invention also provides a wear-resistant braided ceramic material, which is prepared by the preparation method of the wear-resistant braided ceramic material.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The wear-resistant braided ceramic material of the present invention is made by immersing carbon fiber and basalt fiber into a ceramic body, and then orthogonally braiding and finally sintering to obtain the braided ceramic material. The braided ceramic material has improved balance in wear resistance, toughness and anti-fouling properties, and the product has excellent UV resistance and cold and hot cycle stability.
[0037] The ceramic body is prepared by co-mixing boron nitride, aluminum oxide, tungsten carbide, zirconium oxide, additives of modified nano titanium dioxide and ball-milled leveling liquid. The additives of modified nano titanium dioxide are prepared by preheating nano titanium dioxide, coordinating with citric acid and modified nano silica sol. The nano silica sol in the modified nano silica sol, chitosan solution with a mass fraction of 2-5% and sodium alginate solution with a mass fraction of 6% are fully stirred to obtain modified nano silica sol. Nano titanium dioxide is dispersed in the modified nano silica sol to optimize the coordination effect between the additive and the nano titanium dioxide modified liquid. The nano sericite in the additive is treated with hydrogen peroxide solution and proton irradiation to enhance the activity of the nano sericite. The lanthanum chloride solution, silicon micropowder and dopamine hydrochloride solution are mixed and stirred for modification, so that the additive and the nano titanium dioxide modified liquid can be better coordinated and matched, thereby reinforcing the performance effect of the ceramic body.
[0038] The sodium carboxymethyl cellulose, sodium dodecylbenzene sulfonate solution, silane coupling agent KH550 and sodium citrate solution in the ball milling leveling liquid are used as the compounding materials. The obtained ball milling medium can enhance the dispersibility of the system through the mutual coordination between the raw materials, so that the modified regulator can better play a role in the system. The modified regulator adopts graphene activated by acid solution, and then ball milled by mixing nano whiskers and yttrium nitrate solution. The nano whiskers are blended by nano silicon carbide whiskers and sodium silicate solution. The flaky graphene structure is matched with the whisker structure, and the ball milling leveling liquid is prepared by a specific modified regulator, so that the ball milling leveling liquid can be better coordinated with the additive of doped modified nano titanium dioxide, so that the performance of the product is further improved. DETAILED DESCRIPTION
[0039] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] A method for preparing a wear-resistant braided ceramic material according to the present embodiment comprises the following steps:
[0041] Step 1: Preparation of ceramic body:
[0042] (1) Weigh the raw materials according to weight:
[0043] 15-20 parts of boron nitride, 5-8 parts of aluminum oxide, 4-7 parts of additives for doping and modifying nano titanium dioxide, 2-5 parts of tungsten carbide, 2-4 parts of zirconium oxide and 8-12 parts of ball milling leveling liquid;
[0044] (2) The above raw materials are mixed and ball-milled at a speed of 1500 r / min for 1 h to obtain a ceramic body;
[0045] Step 2: Immersing the carbon fiber and the basalt fiber into the ceramic body for immersion treatment, and after the immersion is completed, an immersed carbon fiber body and an immersed basalt fiber are obtained respectively;
[0046] Step three: three-dimensionally orthogonally weave the immersed carbon fiber body and the immersed basalt fiber, and after weaving, sinter and improve the process to obtain a wear-resistant braided ceramic material.
[0047] The specific steps of the sintering improvement process of this embodiment are:
[0048] First, sinter at 350℃ for 20-30min, then heat to 550-570℃ at a rate of 2-5℃ / min and keep at this temperature for 35min;
[0049] Then, heat up to 1200-1250℃ at a rate of 1-3℃ / min, keep warm for 1h, and finally air cool to room temperature.
[0050] The immersion ultrasonic power of the immersion treatment in step 2 is 450-500W, and the immersion time is 30-50min.
[0051] The preparation method of the synergist of doped modified nano titanium dioxide in this embodiment is:
[0052] S01: Add 2-4 parts of nano-silica sol and 1-3 parts of chitosan solution with a mass fraction of 2-5% to 5-8 parts of sodium alginate solution with a mass fraction of 6% by weight and stir well to obtain modified nano-silica sol;
[0053] S02: preheating nano titanium dioxide at 60-65°C for 10-15 minutes, and heat-insulating to obtain preheated nano titanium dioxide; adding 3-5 parts of preheated nano titanium dioxide and 1-3 parts of citric acid to 4-7 parts of modified nano silica sol by weight, and mixing well to obtain nano titanium dioxide modified liquid;
[0054] S03: Preparation of additives:
[0055] S031: fully stirring the nano-sericite in a sufficient amount of a 5% by mass hydrogen peroxide solution, then washing, filtering, and drying to obtain dried nano-sericite; irradiating the dried nano-sericite in a proton irradiation box at an irradiation power of 350-400 W and an irradiation time of 10-15 min to obtain pretreated nano-sericite;
[0056] S032: adding 4 to 7 parts of pretreated nano-sericite, 2 to 4 parts of lanthanum chloride solution and 2 to 3 parts of silicon powder to 5 to 8 parts of dopamine hydrochloride solution by weight, stirring and modifying, after stirring, filtering and drying to obtain an additive;
[0057] S04: Mix the additive and the nano-titanium dioxide modified liquid in a weight ratio of 5:(2-4) and perform ball milling. After the ball milling is completed, wash with water, filter and dry to obtain the additive of doped modified nano-titanium dioxide.
[0058] The ball milling speed of the mixing ball milling treatment in S04 of this embodiment is 550-650 r / min, and the ball milling is 1-2 hours.
[0059] The mass fraction of the lanthanum chloride solution of the present embodiment is 2-4%; the mass fraction of the dopamine hydrochloride solution is 4-6%; the stirring speed of the stirring modification treatment is 450-500r / min, and the stirring time is 35-40min.
[0060] The preparation method of the ball milling leveling liquid of this embodiment is:
[0061] S11: prepare 3-5% by mass sodium dodecylbenzene sulfonate solution and 6% by mass sodium citrate solution;
[0062] S12: 2 to 5 parts of sodium carboxymethyl cellulose, 3 to 5 parts of sodium dodecylbenzene sulfonate solution, 1 to 2 parts of silane coupling agent KH550 and 2 to 4 parts of sodium citrate solution are uniformly stirred by weight to obtain a ball milling medium;
[0063] S13: The modified regulator and the ball milling medium are stirred and mixed thoroughly in a weight ratio of 2:5 to obtain a ball milling leveling solution.
[0064] The preparation method of the modified regulator of this embodiment is:
[0065] The graphene is first stirred in a sufficient amount of acid solution, then washed with water, filtered and dried to obtain dry graphene; 3-5 parts of dried graphene, 1-2 parts of nano whiskers and 5-8 parts of yttrium nitrate solution are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours, and after the ball-milling is completed, washed with water, filtered and dried to obtain a modified regulator;
[0066] The preparation method of the nano whisker body is as follows: nano silicon carbide whiskers and sodium silicate solution are mixed thoroughly in a weight ratio of 2:5 to obtain the nano whisker body.
[0067] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium silicate solution is 3-4%.
[0068] The acid solution of this embodiment is a sulfuric acid solution with a mass fraction of 5%.
[0069] The wear-resistant braided ceramic material of this embodiment is prepared by the above-mentioned method for preparing a wear-resistant braided ceramic material.
[0070] Embodiment 1: A method for preparing a wear-resistant braided ceramic material, comprising the following steps:
[0071] Step 1: Preparation of ceramic body:
[0072] (1) Weigh the raw materials according to weight:
[0073] 15 parts of boron nitride, 5 parts of aluminum oxide, 4 parts of additives for doping and modifying nano titanium dioxide, 2 parts of tungsten carbide, 2 parts of zirconium oxide and 8 parts of ball milling leveling liquid;
[0074] (2) The above raw materials are mixed and ball-milled at a speed of 1500 r / min for 1 h to obtain a ceramic body;
[0075] Step 2: Immersing the carbon fiber and the basalt fiber into the ceramic body for immersion treatment, and after the immersion is completed, an immersed carbon fiber body and an immersed basalt fiber are obtained respectively;
[0076] Step three: three-dimensionally orthogonally weave the immersed carbon fiber body and the immersed basalt fiber, and after weaving, sinter and improve the process to obtain a wear-resistant braided ceramic material.
[0077] The specific steps of the sintering improvement process of this embodiment are:
[0078] First, sinter at 350℃ for 20min, then heat to 550℃ at a rate of 2℃ / min and keep at this temperature for 35min;
[0079] Then, heat up to 1200℃ at a rate of 1℃ / min, keep warm for 1h, and finally air cool to room temperature.
[0080] The immersion ultrasonic power of the immersion treatment in step 2 is 450W, and the immersion time is 30 minutes.
[0081] The preparation method of the synergist of doped modified nano titanium dioxide in this embodiment is:
[0082] S01: Add 2 parts of nano-silica sol and 1 part of chitosan solution with a mass fraction of 2% by weight to 5 parts of sodium alginate solution with a mass fraction of 6% by weight and stir thoroughly to obtain modified nano-silica sol;
[0083] S02: preheating nano titanium dioxide at 60°C for 10 minutes and heat-insulating to obtain preheated nano titanium dioxide; adding 3 parts of preheated nano titanium dioxide and 1 part of citric acid to 4 parts of modified nano silica sol by weight and mixing well to obtain nano titanium dioxide modified liquid;
[0084] S03: Preparation of additives:
[0085] S031: fully stirring the nano-sericite in a sufficient amount of a 5% by mass hydrogen peroxide solution, then washing, filtering, and drying to obtain dried nano-sericite; irradiating the dried nano-sericite in a proton irradiation box at an irradiation power of 350 W and an irradiation time of 10 min to obtain pretreated nano-sericite;
[0086] S032: adding 4 parts of pretreated nano-sericite, 2 parts of lanthanum chloride solution and 2 parts of silicon powder to 5 parts of dopamine hydrochloride solution by weight, stirring and modifying, after stirring, filtering and drying to obtain an additive;
[0087] S04: The additive and the nano-titanium dioxide modified liquid are mixed and ball-milled in a weight ratio of 5:2. After the ball-milling is completed, the mixture is washed with water, filtered and dried to obtain an additive for doping modified nano-titanium dioxide.
[0088] The ball milling speed of the mixing ball milling treatment in S04 of this embodiment is 550 r / min, and the ball milling is performed for 1 hour.
[0089] The mass fraction of the lanthanum chloride solution in this embodiment is 2%; the mass fraction of the dopamine hydrochloride solution is 4%; the stirring speed of the stirring modification treatment is 450 / min, and the stirring time is 35min.
[0090] The preparation method of the ball milling leveling liquid of this embodiment is:
[0091] S11: prepare 3% by mass sodium dodecylbenzene sulfonate solution and 6% by mass sodium citrate solution;
[0092] S12: 2 parts of sodium carboxymethyl cellulose, 3 parts of sodium dodecylbenzene sulfonate solution, 1 part of silane coupling agent KH550 and 2 parts of sodium citrate solution are mixed uniformly by weight to obtain a ball milling medium;
[0093] S13: The modified regulator and the ball milling medium are stirred and mixed thoroughly in a weight ratio of 2:5 to obtain a ball milling leveling solution.
[0094] The preparation method of the modified regulator of this embodiment is:
[0095] The graphene is first stirred in a sufficient amount of acid solution, then washed with water, filtered and dried to obtain dry graphene; 3 parts of dried graphene, 1 part of nano whiskers and 5 parts of yttrium nitrate solution are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours, and after the ball-milling is completed, washed with water, filtered and dried to obtain a modified regulator;
[0096] The preparation method of the nano whisker body is as follows: nano silicon carbide whiskers and sodium silicate solution are mixed thoroughly in a weight ratio of 2:5 to obtain the nano whisker body.
[0097] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium silicate solution is 3%.
[0098] The acid solution of this embodiment is a sulfuric acid solution with a mass fraction of 5%.
[0099] The wear-resistant braided ceramic material of this embodiment is prepared by the above-mentioned method for preparing a wear-resistant braided ceramic material.
[0100] Embodiment 2: A method for preparing a wear-resistant braided ceramic material, comprising the following steps:
[0101] Step 1: Preparation of ceramic body:
[0102] (1) Weigh the raw materials according to weight:
[0103] 20 parts of boron nitride, 8 parts of aluminum oxide, 7 parts of additives for doping and modifying nano titanium dioxide, 5 parts of tungsten carbide, 4 parts of zirconium oxide and 12 parts of ball milling leveling liquid;
[0104] (2) The above raw materials are mixed and ball-milled at a speed of 1500 r / min for 1 h to obtain a ceramic body;
[0105] Step 2: Immersing the carbon fiber and the basalt fiber into the ceramic body for immersion treatment, and after the immersion is completed, an immersed carbon fiber body and an immersed basalt fiber are obtained respectively;
[0106] Step three: three-dimensionally orthogonally weave the immersed carbon fiber body and the immersed basalt fiber, and after weaving, sinter and improve the process to obtain a wear-resistant braided ceramic material.
[0107] The specific steps of the sintering improvement process of this embodiment are:
[0108] First, sinter at 350℃ for 30min, then heat to 570℃ at a rate of 5℃ / min and keep at this temperature for 35min;
[0109] Then, heat up to 1250℃ at a rate of 3℃ / min, keep warm for 1h, and finally air cool to room temperature.
[0110] The immersion ultrasonic power of the immersion treatment in step 2 is 500W, and the immersion time is 50min.
[0111] The preparation method of the synergist of doped modified nano titanium dioxide in this embodiment is:
[0112] S01: Add 4 parts of nano-silica sol and 3 parts of chitosan solution with a mass fraction of 5% by weight to 8 parts of sodium alginate solution with a mass fraction of 6% by weight and stir thoroughly to obtain modified nano-silica sol;
[0113] S02: preheating nano titanium dioxide at 65°C for 15 minutes and heat-insulating to obtain preheated nano titanium dioxide; adding 5 parts of preheated nano titanium dioxide and 3 parts of citric acid to 7 parts of modified nano silica sol by weight and mixing well to obtain nano titanium dioxide modified liquid;
[0114] S03: Preparation of additives:
[0115] S031: fully stirring the nano-sericite in a sufficient amount of a 5% by mass hydrogen peroxide solution, then washing, filtering, and drying to obtain dried nano-sericite; irradiating the dried nano-sericite in a proton irradiation box at an irradiation power of 400 W for 15 minutes to obtain pretreated nano-sericite;
[0116] S032: adding 7 parts of pretreated nano-sericite, 4 parts of lanthanum chloride solution and 3 parts of silicon powder to 8 parts of dopamine hydrochloride solution by weight, stirring and modifying, after stirring, filtering and drying to obtain an additive;
[0117] S04: The additive and the nano-titanium dioxide modified liquid are mixed in a weight ratio of 5:4 and subjected to ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain an additive for doping modified nano-titanium dioxide.
[0118] The ball milling speed of the mixing ball milling treatment in S04 of this embodiment is 650r / min, and the ball milling is performed for 2h.
[0119] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the dopamine hydrochloride solution is 6%; the stirring speed of the stirring modification treatment is 500r / min, and the stirring time is 40min.
[0120] The preparation method of the ball milling leveling liquid of this embodiment is:
[0121] S11: prepare 5% by mass sodium dodecylbenzene sulfonate solution and 6% by mass sodium citrate solution;
[0122] S12: 5 parts of sodium carboxymethyl cellulose, 5 parts of sodium dodecylbenzene sulfonate solution, 2 parts of silane coupling agent KH550 and 4 parts of sodium citrate solution are uniformly stirred according to weight to obtain a ball milling medium;
[0123] S13: The modified regulator and the ball milling medium are stirred and mixed thoroughly in a weight ratio of 2:5 to obtain a ball milling leveling solution.
[0124] The preparation method of the modified regulator of this embodiment is:
[0125] The graphene is first stirred in a sufficient amount of acid solution, then washed with water, filtered and dried to obtain dry graphene; 5 parts of dried graphene, 2 parts of nano whiskers and 8 parts of yttrium nitrate solution are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours, and after the ball-milling is completed, washed with water, filtered and dried to obtain a modified regulator;
[0126] The preparation method of the nano whisker body is as follows: nano silicon carbide whiskers and sodium silicate solution are mixed thoroughly in a weight ratio of 2:5 to obtain the nano whisker body.
[0127] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium silicate solution is 4%.
[0128] The acid solution of this embodiment is a sulfuric acid solution with a mass fraction of 5%.
[0129] The wear-resistant braided ceramic material of this embodiment is prepared by the above-mentioned method for preparing a wear-resistant braided ceramic material.
[0130] Embodiment 3: A method for preparing a wear-resistant braided ceramic material, comprising the following steps:
[0131] Step 1: Preparation of ceramic body:
[0132] (1) Weigh the raw materials according to weight:
[0133] 17.5 parts of boron nitride, 6.5 parts of aluminum oxide, 5.5 parts of additives for doping and modifying nano titanium dioxide, 3.5 parts of tungsten carbide, 3 parts of zirconium oxide and 10 parts of ball milling leveling liquid;
[0134] (2) The above raw materials are mixed and ball-milled at a speed of 1500 r / min for 1 h to obtain a ceramic body;
[0135] Step 2: Immersing the carbon fiber and the basalt fiber into the ceramic body for immersion treatment, and after the immersion is completed, an immersed carbon fiber body and an immersed basalt fiber are obtained respectively;
[0136] Step three: three-dimensionally orthogonally weave the immersed carbon fiber body and the immersed basalt fiber, and after weaving, sinter and improve the process to obtain a wear-resistant braided ceramic material.
[0137] The specific steps of the sintering improvement process of this embodiment are:
[0138] First, sinter at 350℃ for 25min, then heat to 560℃ at a rate of 3.5℃ / min and keep at this temperature for 35min;
[0139] Then, heat it to 1225℃ at a rate of 2℃ / min, keep it warm for 1h, and finally air cool it to room temperature.
[0140] The immersion ultrasonic power of the immersion treatment in step 2 is 475W, and the immersion time is 40min.
[0141] The preparation method of the synergist of doped modified nano titanium dioxide in this embodiment is:
[0142] S01: Add 3 parts of nano-silica sol and 2 parts of chitosan solution with a mass fraction of 3.5% by weight to 6.5 parts of sodium alginate solution with a mass fraction of 6% by weight and stir well to obtain modified nano-silica sol;
[0143] S02: preheating nano titanium dioxide at 62°C for 12.5 minutes and heat-insulating to obtain preheated nano titanium dioxide; adding 4 parts of preheated nano titanium dioxide and 2 parts of citric acid to 5.5 parts of modified nano silica sol by weight and mixing well to obtain nano titanium dioxide modified liquid;
[0144] S03: Preparation of additives:
[0145] S031: fully stirring the nano-sericite in a sufficient amount of a 5% by mass hydrogen peroxide solution, then washing, filtering, and drying to obtain dried nano-sericite; irradiating the dried nano-sericite in a proton irradiation box at an irradiation power of 350 W and an irradiation time of 12.5 min to obtain pretreated nano-sericite;
[0146] S032: adding 5.5 parts of pretreated nano-sericite, 3 parts of lanthanum chloride solution and 2.5 parts of silicon powder by weight to 6.5 parts of dopamine hydrochloride solution and stirring for modification treatment, after stirring, filtering and drying to obtain an additive;
[0147] S04: The additive and the nano-titanium dioxide modified liquid are mixed in a weight ratio of 5:3 and subjected to ball milling. After the ball milling is completed, the mixture is washed with water, filtered and dried to obtain an additive for doping modified nano-titanium dioxide.
[0148] The ball milling speed of the mixing ball milling treatment in S04 of this embodiment is 600 r / min, and the ball milling is performed for 1.5 h.
[0149] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the dopamine hydrochloride solution is 5%; the stirring speed of the stirring modification treatment is 470r / min, and the stirring time is 37.5min.
[0150] The preparation method of the ball milling leveling liquid of this embodiment is:
[0151] S11: prepare 4% by mass sodium dodecylbenzene sulfonate solution and 6% by mass sodium citrate solution;
[0152] S12: 3.5 parts of sodium carboxymethyl cellulose, 4 parts of sodium dodecylbenzene sulfonate solution, 1.5 parts of silane coupling agent KH550 and 3 parts of sodium citrate solution were mixed uniformly by weight to obtain a ball milling medium;
[0153] S13: The modified regulator and the ball milling medium are stirred and mixed thoroughly in a weight ratio of 2:5 to obtain a ball milling leveling solution.
[0154] The preparation method of the modified regulator of this embodiment is:
[0155] The graphene is first stirred in a sufficient amount of acid solution, then washed with water, filtered and dried to obtain dried graphene; 4 parts of dried graphene, 1.5 parts of nano whiskers and 6.5 parts of yttrium nitrate solution are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours, and after the ball-milling is completed, washed with water, filtered and dried to obtain a modified regulator;
[0156] The preparation method of the nano whisker body is as follows: nano silicon carbide whiskers and sodium silicate solution are mixed thoroughly in a weight ratio of 2:5 to obtain the nano whisker body.
[0157] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium silicate solution is 3.5%.
[0158] The acid solution of this embodiment is a sulfuric acid solution with a mass fraction of 5%.
[0159] The wear-resistant braided ceramic material of this embodiment is prepared by the above-mentioned method for preparing a wear-resistant braided ceramic material.
[0160] Comparative Example 1:
[0161] The difference from Example 3 is that no additive for doping and modifying nano titanium dioxide is added in the preparation of the ceramic body.
[0162] Comparative Example 2:
[0163] The difference from Example 3 is that no nano-titanium dioxide modifying liquid is added in the preparation of the additive for doping and modifying nano-titanium dioxide.
[0164] Comparative Example 3:
[0165] The difference from Example 3 is that no preheated nano-titanium dioxide and citric acid are added in the preparation of the nano-titanium dioxide modified solution.
[0166] Comparative Example 4:
[0167] The difference from Example 3 is that no modified nano-silica sol is added in the preparation of the nano-titanium dioxide modified solution.
[0168] Comparative Example 5:
[0169] The difference from Example 3 is that no additive is added in the preparation of the additive for doping and modifying nano titanium dioxide.
[0170] Comparative Example 6:
[0171] The difference from Example 3 is that no lanthanum chloride solution and silicon powder are added in the preparation of the additive.
[0172] Comparative Example 7:
[0173] The difference from Example 3 is that no pretreated nano-sericite and dopamine hydrochloride solution are added in the preparation of the additive.
[0174] Comparative Example 8:
[0175] The difference from Example 3 is that no ball milling leveling liquid is added.
[0176] Comparative Example 9:
[0177] The difference from Example 3 is that in the preparation of the ball milling leveling solution, the ball milling medium is replaced by a sodium citrate solution with a mass fraction of 6%.
[0178] Comparative Example 10:
[0179] The difference from Example 3 is that no modifying regulator is added in the preparation of the ball milling leveling solution.
[0180] Comparative Example 11:
[0181] The difference from Example 3 is that no nano whiskers are added in the preparation of the modified regulator.
[0182] Comparative Example 12:
[0183] The difference from Example 3 is that the nano whisker body is replaced by nano silicon carbide whiskers.
[0184] Comparative Example 13:
[0185] The difference from Example 3 is that no dry graphene is added in the preparation of the modified regulator.
[0186] Comparative Example 14:
[0187] The difference from Example 3 is that deionized water is used instead of yttrium nitrate solution in the preparation of the modified regulator.
[0188] The products of Examples 1 to 3 and Comparative Examples 1 to 14 were tested under normal conditions, and the products were heat treated at 70°C for 12 hours, then placed at -5°C for 12 hours, and then exposed to ultraviolet light at an intensity of 200 mj / m 2 The product was irradiated for 1 hour under the conditions of , the above is one cycle, and a total of 10 cycles were performed. After the cycle was completed, the product's UV and cold and hot cycle stability were tested. The test results are shown in Table 1.
[0189] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 14:
[0190]
[0191] It can be seen from Comparative Examples 1-14 and Examples 1-3 that the product of Example 3 has excellent wear resistance, toughness and anti-fouling properties, and the three properties can be improved in a coordinated manner. In addition, the product has excellent stability under ultraviolet and cold and heat cycle conditions;
[0192] It can be seen from Comparative Example 1, Comparative Example 8 and Example 3 that the performance of the product deteriorates significantly when no additive for doping modified nano titanium dioxide and no ball milling leveling liquid are added in the preparation of the ceramic body. The performance of the product is significantly improved by using the synergistic combination of the two.
[0193] It can be seen from Comparative Examples 1-7 and Example 3 that the performance of the products tended to deteriorate when no nano-titanium dioxide modifying liquid was added in the preparation of the additive for doping modified nano-titanium dioxide, and no additive was added in the preparation of the additive for doping modified nano-titanium dioxide. In addition, the performance of the products tended to deteriorate when no preheated nano-titanium dioxide and citric acid were added in the preparation of the nano-titanium dioxide modifying liquid, no modified nano-silica sol was added in the preparation of the nano-titanium dioxide modifying liquid, no lanthanum chloride solution and silicon powder were added in the preparation of the additive, and no pretreated nano-sericite and dopamine hydrochloride solution were added in the preparation of the additive.
[0194] The nano titanium dioxide modified liquid obtained by the specific method of the present invention is combined with the special additives of the present invention, and the performance effect of the product is the most significant. The effect of the present invention is not as obvious as that of other methods.
[0195] From Comparative Examples 9-10 and Example 3, it can be seen that the ball milling medium in the preparation of the ball milling leveling solution is replaced by a sodium citrate solution with a mass fraction of 6%, and no modifying regulator is added in the preparation of the ball milling leveling solution, and the performance of the product tends to deteriorate;
[0196] It can be seen from Comparative Examples 11-14 and Example 3 that the performance of the products tended to deteriorate to varying degrees when no nano whiskers were added to the preparation of the modified regulator, nano whiskers were replaced by nano silicon carbide whiskers, dry graphene was not added to the preparation of the modified regulator, and yttrium nitrate solution was replaced by deionized water in the preparation of the modified regulator.
[0197] Only the ball milling leveling liquid obtained by combining the modified regulator obtained by the specific method of the present invention with the ball milling medium can produce the most significant product performance effect. Other methods are not as obvious as the effect of the present invention.
[0198] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0199] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a wear-resistant braided ceramic material, characterized in that: The following steps are involved: Step 1: Preparation of ceramic body: Weigh the raw materials according to weight: 15-20 parts of boron nitride, 5-8 parts of aluminum oxide, 4-7 parts of additives for doping and modifying nano titanium dioxide, 2-5 parts of tungsten carbide, 2-4 parts of zirconium oxide and 8-12 parts of ball milling leveling liquid; The preparation method of the synergist of the doped modified nano titanium dioxide is as follows: S01: Add 2-4 parts of nano-silica sol and 1-3 parts of chitosan solution with a mass fraction of 2-5% to 5-8 parts of sodium alginate solution with a mass fraction of 6% by weight and stir well to obtain modified nano-silica sol; S02: preheating nano titanium dioxide at 60-65°C for 10-15 minutes, and heat-insulating to obtain preheated nano titanium dioxide; adding 3-5 parts of preheated nano titanium dioxide and 1-3 parts of citric acid to 4-7 parts of modified nano silica sol by weight, and mixing well to obtain nano titanium dioxide modified liquid; S03: Preparation of additives: S031: fully stirring the nano-sericite in a sufficient amount of a 5% by mass hydrogen peroxide solution, then washing, filtering, and drying to obtain dried nano-sericite; irradiating the dried nano-sericite in a proton irradiation box at an irradiation power of 350-400 W and an irradiation time of 10-15 min to obtain pretreated nano-sericite; S032: adding 4 to 7 parts of pretreated nano-sericite, 2 to 4 parts of lanthanum chloride solution and 2 to 3 parts of silicon powder to 5 to 8 parts of dopamine hydrochloride solution by weight, stirring and modifying, after stirring, filtering and drying to obtain an additive; S04: mixing the additive and the nano-titanium dioxide modified liquid in a weight ratio of 5:(2-4) and subjecting them to ball milling. After the ball milling is completed, washing, filtering and drying are performed to obtain the additive for doping modified nano-titanium dioxide. The preparation method of the ball milling leveling liquid is as follows: S11: prepare 3-5% by mass sodium dodecylbenzene sulfonate solution and 6% by mass sodium citrate solution; S12: 2 to 5 parts of sodium carboxymethyl cellulose, 3 to 5 parts of sodium dodecylbenzene sulfonate solution, 1 to 2 parts of silane coupling agent KH550 and 2 to 4 parts of sodium citrate solution are uniformly stirred by weight to obtain a ball milling medium; S13: stirring and mixing the modified regulator and the ball milling medium in a weight ratio of 2:5 to obtain a ball milling leveling solution; The preparation method of the modified regulator is: The graphene is first stirred in a sufficient amount of acid solution, then washed with water, filtered and dried to obtain dry graphene; 3-5 parts of dried graphene, 1-2 parts of nano whiskers and 5-8 parts of yttrium nitrate solution are mixed and ball-milled by weight at a ball-milling speed of 1000 r / min for 2 hours, and after the ball-milling is completed, washed with water, filtered and dried to obtain a modified regulator; The preparation method of the nano whisker body is as follows: nano silicon carbide whiskers and sodium silicate solution are mixed thoroughly in a weight ratio of 2:5 to obtain the nano whisker body; The above raw materials were mixed and ball-milled at a speed of 1500 r / min for 1 h to obtain a ceramic body; Step 2: Immersing the carbon fiber and the basalt fiber into the ceramic body for immersion treatment, and after the immersion is completed, an immersed carbon fiber body and an immersed basalt fiber are obtained respectively; Step three: three-dimensionally orthogonally weave the immersed carbon fiber body and the immersed basalt fiber, and after weaving, sinter and improve the process to obtain a wear-resistant braided ceramic material.
2. The method for preparing a wear-resistant braided ceramic material according to claim 1, characterized in that: The specific steps of the sintering improvement process are: First, sinter at 350℃ for 20-30min, then heat to 550-570℃ at a rate of 2-5℃ / min and keep at this temperature for 35min; Then, heat up to 1200-1250℃ at a rate of 1-3℃ / min, keep warm for 1h, and finally air cool to room temperature. The immersion ultrasonic power of the immersion treatment in step 2 is 450-500W, and the immersion time is 30-50min.
3. The method for preparing a wear-resistant braided ceramic material according to claim 1, characterized in that: The ball milling speed of the mixing ball milling treatment in S04 is 550-650 r / min, and the ball milling is performed for 1-2 hours.
4. The method for preparing a wear-resistant braided ceramic material according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 2-4%; the mass fraction of the dopamine hydrochloride solution is 4-6%; the stirring speed of the stirring modification treatment is 450-500 r / min, and the stirring time is 35-40 min.
5. The method for preparing a wear-resistant braided ceramic material according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium silicate solution is 3-4%.
6. The method for preparing a wear-resistant braided ceramic material according to claim 1, characterized in that: The acid solution is a sulfuric acid solution with a mass fraction of 5%.
7. A wear-resistant braided ceramic material prepared by the method for preparing a wear-resistant braided ceramic material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Ceramic friction material and preparing method thereof
CN108083831A
Abrasion-resistant and anti-corrosion braided ceramic composite, forming method thereof and braided ceramic product
CN109400195A